Final Overall Survival Analysis of the TOURMALINE-MM1 Phase III Trial of Ixazomib, Lenalidomide, and Dexamethasone in Patients With Relapsed or Refractory Multiple Myeloma. Issue 22 (1st August 2021) - Richardson, Paul G.; Kumar, Shaji K.; Masszi, Tamás; Grzasko, Norbert; Bahlis, Nizar J.; Hansson, Markus; Pour, Luděk; Sandhu, Irwindeep; Ganly, Peter; Baker, Bartrum W.; Jackson, Sharon R.; Stoppa, Anne-Marie; et al.
Abstract : PURPOSE: The double-blind, placebo-controlled, phase III TOURMALINE-MM1 study demonstrated a statistically significant improvement in progression-free survival with ixazomib-lenalidomide-dexamethasone (ixazomib-Rd) versus placebo-Rd in patients with relapsed or refractory multiple myeloma. We report the final analyses for overall survival (OS). PATIENTS AND METHODS: Patients were randomly assigned to ixazomib-Rd (n = 360) or placebo-Rd (n = 362), stratified by number of prior therapies (1 v 2 or 3), previous proteasome inhibitor (PI) exposure (yes v no), and International Staging System disease stage (I or II v III). OS (intent-to-treat population) was a key secondary end point. RESULTS: With a median follow-up of 85 months, median OS with ixazomib-Rd versus placebo-Rd was 53.6 versus 51.6 months (hazard ratio, 0.939; P = .495). Lower hazard ratios, indicating larger magnitude of OS benefit with ixazomib-Rd versus placebo-Rd, were seen in predefined subgroups: refractory to any (0.794) or last (0.742) treatment line; age > 65-75 years (0.757); International Staging System stage III (0.779); 2/3 prior therapies (0.845); high-risk cytogenetics (0.870); and high-risk cytogenetics and/or 1q21 amplification (0.862). Following ixazomib-Rd versus placebo-Rd, 71.7% versus 69.9% of patients received ≥ 1 anticancer therapy, of whom 24.7% versus 33.9% received daratumumab and 71.8% versus 76.9% received PIs (next-line therapy: 47.5% v 55.8%). Rates of new primary malignancies were similar with ixazomib-Rd (10.3%) and placebo-Rd (11.9%). There were no new or additional safety concerns. CONCLUSION: Median OS values in both arms were the longest reported in phase III studies of Rd-based triplets in relapsed or refractory multiple myeloma at the time of this analysis; progression-free survival benefit with ixazomib-Rd versus placebo-Rd did not translate into a statistically significant OS benefit on intent-to-treat analysis. OS benefit was greater in subgroups with adverse prognostic factors. OS interpretation was confounded by imbalances in subsequent therapies received, especially PIs and daratumumab.